PENGARUH PERPUTARAN PERSEDIAAN DAN PERPUTARAN AKTIVA TETAP TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marfina Agustina; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of inventory turnover and fixed assets on profitability in automotive and component companies. The population in this study are automotive and component companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this study used purposive sampling technique and obtained a sample of 8 companies. Analysis of the data used is multiple linear regression. From the analysis results show that the results partially (t test) inventory turnover variable has no effect on Profitability (ROI) and fixed asset turnover has an effect on Profitability (ROI). Simultaneous results (F test) show that all independent variables have an effect on profitability (ROI). The adjusted R square value is 0.534. This means that 53.4% of the profitability variable is influenced by two independent variables, turnover [inventory] and fixed asset turnover. While the remaining 46.6% is influenced by variables that are not examinedKeywords : Inventory Turnover, Fixed Asset Turnover, Profitability (ROI)